Bearing Capacity and Deformation of Micropiles Considering Plastic Hinge - Yipaliya Abuduweili; Li Ma; Kaixin Shi; Xinlin Zhu (Buildings)
This study systematically investigates the plastic deformation behavior and load-bearing mechanisms of micropiles through integrated scaled physical modeling and nonlinear finite element analysis, with particular emphasis on quantifying plastic hinge characteristics. The development of plastic deformation in laterally loaded micropiles was analytically described using plastic hinge theory, complemented by experimental-numerical validation. The key findings demonstrate the following points. (1) Existing empirical formulas for plastic hinge length, based on sectional parameters, show significant discrepancies, with experimental calibration establishing an optimized length of 2D. (2) Parametric FEM studies of three diameter groups (3–7% longitudinal reinforcement ratio) reveal that cross-sectional geometry and reinforcement configuration collectively govern nonlinear ultimate capacity, where ≤0.1% reinforcement ratio variation induces <5% bearing capacity deviation. (3) Square sections exhibit 12–18% higher capacity than circular equivalents of the equivalent dimensions, with this advantage amplifying with increasing pile size. (4) While excessive reinforcement ratios (>6%) impair structural performance, emergent scale effects effectively mitigate associated capacity reduction. These findings provide critical insights for optimizing micropile design in geotechnical applications through coordinated consideration of geometric, material, and scale parameters.